2009
DOI: 10.1007/s11205-009-9539-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Internet Connectedness and Information Literacy on Quality of Life

Abstract: Internet connectedness, Information literacy, Quality of life (QoL),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 37 publications
2
37
0
4
Order By: Relevance
“…Madon [59] claimed the requirement to afford wider connectivity that would increase global information infrastructure and support positive changes in socio-economic development. Accordingly, Leung [60] reported a significant association between Internet connectedness and information literacy. Based on the evidence from 21 OECD countries over 1970-1990, Roller and Waverman [61] unveiled a significant positive causal link between investment in telecommunication infrastructure and subsequent economic performance.…”
Section: The Impact Of Infrastructure and Technology On Sustainable Ecomentioning
confidence: 98%
“…Madon [59] claimed the requirement to afford wider connectivity that would increase global information infrastructure and support positive changes in socio-economic development. Accordingly, Leung [60] reported a significant association between Internet connectedness and information literacy. Based on the evidence from 21 OECD countries over 1970-1990, Roller and Waverman [61] unveiled a significant positive causal link between investment in telecommunication infrastructure and subsequent economic performance.…”
Section: The Impact Of Infrastructure and Technology On Sustainable Ecomentioning
confidence: 98%
“…Partly because of the limitation of time-based measures (e.g., hours of Internet use per day), which ignore the importance of other contexts such as goals or functions, Jung et al (2001) developed a measure called the Internet connectedness index (ICI) based on media system dependency theory (Ball-Rokeach, 1998;Loges & Jung, 2001). The ICI encompasses a number of conventional measures, such as time and history, yet also goes beyond to capture the Internet's scope, goal, intensity, and centrality in a person's life Leung, 2010).…”
Section: Theoretical Framework Ict Connectedness (Ictc)mentioning
confidence: 99%
“…Leung showed that there was a significant relationship between internet connectivity with information literacy and a strong relationship between information literacy and quality of life [17]. These findings encourage that the use of communication media has a positive impact on the quality of life of a person as long as the media is used with good intentions [8], [18]- [20].…”
Section: Introductionmentioning
confidence: 92%